IMPORTANCE OF ENVIRONMENTAL ECONOMICS FOR AGRICULTURAL LAND DEVELOPMENT - Sharyi Г.; Shchepak В.; Yermakova І.; Odariuk Т. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The work examines the significance of economic doctrines and theories in shaping the field of environmental economics. It considers scientific approaches to the utilization of natural resource potential by the economy, along with the contributions of economic theories to the development of agricultural land. The current state of geopolitical economic opportunism in numerous countries adversely affects the consumption of natural resources, leading to a deterioration of natural resource potential, particularly in terms of the natural fertility of agricultural land. Such opportunistic exploitation of natural resources by the economy has detrimental consequences for the natural resource base, especially regarding agricultural land. A structural and logical model for the functioning of environmental economic systems is proposed, with its components grouped into two categories. The first group encompasses natural resources - particularly agricultural land - and ecology, which includes environmental standards and norms. The second group consists of production methods such as organic agriculture, carbon farming, and green industry, as well as the efficiency of natural resource utilization. The components of the system are interconnected and interdependent. The balance among the components of the environmental economic system is maintained through instruments of ecological equilibrium, which include environmental taxes, rental payments, sanctions, and economic incentives. The impact of these tools leads to greener production practices, the restoration of natural resources, improved soil fertility, and the establishment of ecological well-being, all stemming from the development of natural resource potential. The effective operation of the environmental economic system is grounded in the ecological, economic, and socio-mental institutions of society. States and societies should exert regulatory influence on economic actors to mitigate the negative effects of natural and economic entropy. The paper underscores the crucial importance of economic incentives for achieving ecological neutrality, implementing eco-economic standards, and applying environmental taxes and sanctions, both on business entities and nations identified as ecological aggressors.